Mastering Manga Studio 5 : an extensive, fun, and practical guide to streamlining your comic-making workflow using Manga Studio 5 - Staley, Liz (Community experience distilled., 2013)
Mastering Manga Studio 5 will follow an explanatory, work through manual approach. The main features of Manga will be presented in each section along with exciting tips, vital techniques and impressive workflows. This book is for those who already have some Manga Studio and graphics program experience. It is not a beginner's guide, but if you are a novice Manga Studio 5 user it will help you to master the time-saving features of the software.